The Failed Transition of Serbian Media System - Jevtović, Zoran B.; Bajić, Predrag Đ. (Sociološki pregled, 2019)
The deregulation of media sphere and the transformation of regulatory framework in Serbia has begun at the end of last century with a mission to bring it closer to the developed countries of Europe. However, the process of ownership transformation has only formalized new media monopolies and quality legal solutions were marginalized by poor and inconsistent implementation. The framing of communication images into distorted media frames has strengthened the negative perception in society, because the absence of media diversity in reporting has put very strong tabloid and sensationalist discourses to the forefront. The changes that we are pointing to transform the meaning of a journalistic paradigm. Private media corporations and digitized platforms, increasingly focused on budget funds, construct ideologically desirable narratives, becoming part of the propaganda and clientelist industry.